Factors associated with poor glycemic control in a population of type 2 diabetes in Sub-Saharan - (:unkn) unknown (My University, 2014)
Despite several studies showing the benefits of good glycemic control , it is insufficient for a significant number of adults with type 2 diabetes. Several risk factors are associated with poor glycemic control . Inadequate consideration by patients immediate and long-term poor glycemic control may also play a role. The objectives of this thesis were : determine the frequency of poor glycemic control , defined as a glycated hemoglobin ( HbA1c) ≥ 7.0% in diabetic subjects with type 2 in sub- Saharan Africa ; determine the associations between poor glycemic control and potential risk factors in type 2 diabetes in sub- Saharan Africa ; determine the frequency of symptoms of anxiety and depression and risk factors associated with these conditions in type 2 diabetes in sub- Saharan Africa. Cross-sectional data for inclusion in the study "Improving access to HbA1c in sub- Saharan Africa " conduct in Cameroon and Guinea were used. HbA1c values ​​have allowed the diabetic population dichotomized into two groups: those with good (HbA1c <7.0 %) or those with bad (HbA1c ≥ 7.0%) glycemic control. Models of binary logistic regression were used to assess the relationship between potential risk factors and glycemic control . Analyses were conducted using SAS software . Adjusted for sociodemographic variables , clinical and psychosocial variables varied multi models were produced . The results showed that the percentage of type 2 diabetics with poor glycemic control is higher in Cameroon (68% of subjects with HbA1c ≥ 7.0 %) and Guinea (84% of subjects) . The main predictors of poor glycemic control were highlighted : the inclusion in Guinea, less than 65 years age, duration of more than 2 years known diabetes , treatment with oral anti diabetic with or without insulin and the absence of previous measurements of HbA1c . Symptoms of anxiety and depression in type 2 diabetes were common in Guinea ( respectively 34.4 % and 58.7 % of subjects) . A high H
Keywords: African Research